2004
DOI: 10.1186/1476-4598-3-12
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Wide-spread hypomethylation of CpG dinucleotides is characteristic of many cancers. Retrotransposons have been identified as potential targets of hypomethylation during cellular transformation. We report the results of an preliminary examination of the methylation status of CpG dinucleotides associated with the L1 and HERV-W retrotransposons in benign and malignant human ovarian tumors. We find a reduction in the methylation of CpG dinucleotides within the promoter regions of these retroelements in malignant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…Chromosome deletions and translocations probably caused by retrotransposition events have indeed been observed in several human cancers (Morse et al, 1988;Nagarajan et al, 1990;Miki et al, 1992;Pomykala et al, 1994;Liu et al, 1997). Moreover, a significant increase in the expression of a variety of retrotransposons and direct evidence for the hypomethylation of L1s has been observed during human cellular transformation (Takai et al, 2000;Menendez et al, 2004;Suter et al, 2004). …”
Section: Discussionmentioning
confidence: 97%
“…Chromosome deletions and translocations probably caused by retrotransposition events have indeed been observed in several human cancers (Morse et al, 1988;Nagarajan et al, 1990;Miki et al, 1992;Pomykala et al, 1994;Liu et al, 1997). Moreover, a significant increase in the expression of a variety of retrotransposons and direct evidence for the hypomethylation of L1s has been observed during human cellular transformation (Takai et al, 2000;Menendez et al, 2004;Suter et al, 2004). …”
Section: Discussionmentioning
confidence: 97%
“…HERV-K is thought to be transcriptionally silent in normal cells, and becomes active after malignant transformation (8,11), except in the case of brain tumors (12). Increased expression of HERV-K has been detected in human cancers (8,1321), and transcripts of HERVs have been detected by many independent investigators in various types of cancer that include breast cancer (8,22,23), ovarian cancer (24, 25), lymphoma (26,27), melanoma (11,2832), germ line tumors (3335), and prostate cancer (5, 36). Our laboratory showed that the HERV-K family is active and overexpressed in breast cancer (2,23,3740): HERV-K expression was detected in 45% to 93% of primary breast tumors (N=479), and a higher rate of lymph node metastasis was associated with HERV-K-positive compared with HERV-K-negative tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Likely, the hypomethylation observed in frail subjects can be associated to an accentuated deficiency to achieve the remethylation after DNA replication that, as reported in Gravina and Vijg (2010), occurs during aging. In addition, the above hypomethylation could derepress silenced retrotransposons, such as L1 or IAP, thus inducing genome instability that might account for the decline typical of frailty status (Barbot et al 2002;Menendez et al 2004;Maslov and Vijg 2009). Moreover, longitudinal data provide an important contribution to studies which consider frailty as a dynamic process.…”
Section: Discussionmentioning
confidence: 96%